Development of Highly Selective Support for CO Hydrogenation to Light Olefins with Partially Passivated Iron Catalysts. Issue 14 (18th July 2019) - Xing, Yu; Jia, Gaopeng; Liu, Zhenxin; Fang, Shaoming; Zhao, Chenxi; Guo, Xuehui; Suib, Steven L.
Abstract: The front cover artwork for Issue 14/2019 is provided by researchers from Yu Xing, Zhenxin Liu and co‐workers at the Zhengzhou University of Light Industry (P. R. China) and the University of Connecticut (USA). The image shows that light olefins (ethylene, propylene and butylene) may be selectively generated through conversion of syngas over an iron catalyst with a partially passivated Al–O–Zn support. See the Full Paper itself at https://doi.org/10.1002/cctc.201900023 . Abstract : " Human interest in Fischer‐Tropsch reactions is based on the sustainable use " This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttps://doi.org/10.1002/cctc.201900023 .